Adoption of Decentralized Renewable Energy Solutions by MSMEs: Barriers and Opportunities in India - Mohite, Rohit; Chaurasiya, Ravi; Akre, Sandesh; Joshi, Nirmala; Muley, Harshada; Vasudevan, Asokan (International Journal of Energy Economics and Policy, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are crucial to India’s economic development, yet they face significant energy cost burdens that hinder productivity. Decentralized Renewable Energy (DRE) solutions such as rooftop solar and biomass can reduce operational costs and promote sustainability. This paper investigates the adoption of DRE among 390 Indian MSMEs across multiple sectors using a mixed-methods approach. Quantitative data were analysed using SPSS for trends and barriers, while qualitative interviews enriched the insights on adoption behaviour. The findings reveal that although 65% of MSMEs are aware of DRE, only 48% have adopted it. Major barriers include initial cost, lack of policy clarity, and technical know-how. The paper recommends targeted financial schemes and awareness campaigns to foster DRE adoption. This study contributes to understanding the energy transition pathways for small enterprises in emerging economies.